Differential enrolment and operational cost of public secondary schools in urban and rural Edo State. Nigeria (2014)
This study therefore investigated the differential enrolment and recurrent unit cost of public secondary schools in urban and rural Edo state, Nigeria. The study adopted the descriptive research design of the survey type. The population for the study consisted of all the principals in all the 540 public secondary schools in Edo state. Two hundred and sixteen (216) or 40% of the schools and principals were selected using stratified and simple random sampling techniques. An inventory on school enrolment and operational expenditure mas used to obtain relevant information from the individual schools. Two hundred (200) or 92.5% of the instrument were retuned. The t-statistics analytical tool was used to test the two hypotheses while quadratic equation regression model was used to show the curvilinear relationship between school enrolment and unit cost in the sampled schools. The hypotheses were tested at 5% level of significance. Result of the study showed that there were significant differences in recurrent unit cost (t=2.078; p<0.05) and enrolment (t— 4.48; p<0.05) respectively between urban and rural schools in the state. The relationship between expanding enrolment and recurrent unit cost was U-shaped. Policy towards improving enrolment in rural schools was therefore recommended as a technique for reducing the operational cost of schools